Assessing food security post-earthquake in Majene, Indonesia: An analysis of food availability, consumption patterns, and dietary quality - Karim, Ikawati; Kasmiati, Kasmiati; Hendi, Hendi; Panikkai, Sumarni (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study examines food security in Majene, West Sulawesi, following the 2021 earthquake, focusing on food availability, consumption, and dietary patterns. The research utilizes a descriptive qualitative approach and relies on secondary data from the Food Security Service Office of the Majene Regency. The data are supplemented by information from the Central Statistics Agency and interviews with informants. The findings reveal that the primary nutritional parameters—energy, protein, and fat—are adequately met. The availability of energy from vegetable sources exceeds the recommended 984 kcal/capita/day. Protein availability, mainly from animal sources, meets the 63 grams/capita/day guideline. Fat availability, primarily from vegetable fats, also aligns with the recommended 72.17 grams/capita/day. During the earthquake, food supplies, which included 11 staple types, were sufficient, evidenced by available quantities surpassing consumption levels. For instance, rice availability stood at 29,277 tons against a consumption level of 20,084.70 tons. The study also assesses dietary patterns, finding that grains, oils, fats, oily fruits/seeds, sugars, and vegetables meet desirable dietary scores, while tubers, animal products, and legumes fall short.